Alkaline ball-milled peanut-hull biosorbent effectively removes aqueous organic dyes. (February 2023) - Yang, Xiaodong; Wang, Lili; Tong, Jin; Shao, Xueqin; Feng, Ying; Zhou, Jinfeng; Han, Ye; Yang, Xizhen; Ding, Fangjun; Zhang, Jing; Li, Qiaoyu; Li, Guodong; et al.
Abstract: Advanced biosorbents increasingly attract attention for their application in environment remediation. Here, a facile one-step approach to alkaline ball milling was used to synthesize a porous peanut hull biosorbent without heating. The alkaline ball-milled peanut-hull (ABP) biosorbent was characterized for its ability to remove Congo red (CR), titan yellow (TY), and methyl violet (MV) from aqueous solutions. ABP processed abundant O-containing functional groups and developed porosity, resulting in maximum sorption capacities of 4864.4 (CR), 455.9 (TY), and 126.1 (MV) mg g −1 . Freundlich isotherm and PSO kinetic models best fit the anionic dye's (CR and TY) adsorption by ABP, indicating multiple mechanisms might control the adsorption process. Freundlich and PFO kinetics models best described cationic MV adsorption by ABP, suggesting the adsorption of cationic dye could also be governed by multi-mechanisms but less heterogeneous than that of anionic dye. The results suggest that alkaline ball-milling is promising approach to converting biomass into advanced biosorbents for organic dyes, especially anionic ones. Graphical abstract: Image 1 Highlights: Alkaline ball-milled peanut biosorbent was produced to remove polar organic dyes. ABP sorbed 4864.4 mg g −1 CR and 455.9 mg g −1 TY, superior to other biosorbents. Alkaline treatment optimized ABP's O-containing groups, pore structure, and functionality. Sorption capacity of CR/TY onto ABP was more than 85% after 5 desorption cycles.